1,6-Conjugate addition of zinc alkyls to para-quinone methides in a continuous-flow microreactor† - Jadhav, A.S.; Anand, R.V. (Royal Society of Chemistry, 2017)
An efficient method for the synthesis of alkyl diarylmethanes through the 1,6-conjugate addition of dialkylzinc reagents to para-quinone methides (p-QMs) has been developed under continuous flow conditions using a microreactor. This protocol allows to access unsymmetrical alkyl diarylmethanes in moderate to excellent yields using a wide range of p-QMs and dialkylzinc reagents. Interestingly, this transformation worked well without the requirement of a catalyst.
Keywords: Dialkylzinc; Efficient; Synthesis